Listeners' Perception of the Greatest Memory Radio Yasika FM Jogja Broadcast Program - Kurniawati, Ninda; Prismarini, Rosa; Nuryana, Arief (Indonesian Journal of Advanced Research, 2024)
Listener perception is crucial for a program's sustainability. This study aims to understand listener perceptions of the Greatest Memory program on Radio Yasika FM Jogja. Using a descriptive qualitative method and perception analysis, the study involved followers of @greatestmemories_id on Instagram as subjects. Findings reveal that listener perceptions are generally consistent and fall within the latitude of acceptance, indicating positive evaluations. However, statements from informants Ana Musiam and Bagas Fernando fall in the latitude of non-commitment, reflecting varied perceptions based on their individual thoughts, experiences, and views. Overall, most informants express acceptance and favorable perceptions of the program, demonstrating its effectiveness in meeting audience expectations.